2018
DOI: 10.1293/tox.2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of long-term stored formalin-fixed paraffin embedded tissues for histopathological evaluation

Abstract: Histopathological examination of formalin-fixed paraffin-embedded (FFPE) tissues that had been stored for 30 years was conducted, and reconstructivity of the results was verified. These FFPE tissues, which were from all organs of male and female rats, were re-sectioned and histopathologically examined using hematoxylin and eosin (HE) staining. In particular, the stainability and morphology of HE sections and reproducibility of microscopic findings in the liver and kidney demonstrated in the original final repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Quality of formalin fixed tissues stored for 30 years in rat specimen for histopathological analysis reported fading in staining and few morphological artifacts and concluded that their results were favorable and comparable to their original histopathological reports. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality of formalin fixed tissues stored for 30 years in rat specimen for histopathological analysis reported fading in staining and few morphological artifacts and concluded that their results were favorable and comparable to their original histopathological reports. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in staining quality in LFT from our study can be related to stainability and microscopic findings in liver, kidney and other organs assessed in rat tissues that were stored for 30 years. [ 8 ] Less satisfactory staining of prolonged formalin-fixed tissues than paraffin embedded blocks is due to excessive cross-linking of proteins and production of formic acid which lowers the pH of formalin fixative solution in which tissues are preserved for prolonged duration. Staining adequacy of the tissue sections for H&E, was found to be superior as compared to Mallory's stain and Van Gieson's stain.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that the tissues can be affected by different factors at the time of preparation of the samples. Tissue manipulation during surgery, formalin fixation, paraffin embedment, and storage methods are conditions that impact the quality of the histological specimen [29, 30], which could limit the improvement of histopathological studies.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the quality of FFPE biospecimens, often stored over a long-term period, needs to be critically evaluated to determine their fit-for-purpose for accurate molecular phenotyping. While formalin fixation and paraffin embedding preserves tissue morphology for up to 30 years of storage [ 90 ], including cytological details and immune-reactivity of tissue antigens, recent studies investigate the influence of long-term storage on complex molecular analytes. Results, however, are somehow controversial with studies concluding that the fitness of FFPE blocks for proteomic analysis is independent of tissue age evaluating a time frame of 11 years [ 91 ], respectively 11-year intervals from 1990 to 2001 and from 2002 to 2013 [ 92 ], but rather dependent on tissue and tumor type, reporting significant differences in protein derivatives between papillary, squamous, and adenocarcinomas as measured by protein absorbance values in one of the studies [ 92 ].…”
Section: Postsurgical Factors Confounding Biospecimen Qualitymentioning
confidence: 99%